ปัจจัยที่มีผลต่อการยอมรับและสนับสนุนองค์กรไม่แสวงหากําไร : กรณีศึกษาการพัฒนาศูนย์วิจัยกีฏวิทยาป่าไม้ที่ 1 จังหวัดลําปาง - ศตวรรษ วรรณพันธ์ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2018)
Non – profit organization followed public economics named Entomology Research Center 1 was located in Nqao district, Lampang Thailand. The objective of this research was to explore the factor affecting for adoption and support this center’s development. Research methodology was used primary data by questionnaires creation. The data was collected from 500 samples of people in Lampang province. A sample of people in Lampang cases were drawn from using stratified random sampling. This cross – section data surveyed during from January – March, 2014. Firstly, the analysis on general data was derived into two sample groups: adoption (440 samples) and non – adoption (60 samples). After that, the demographic and socio – economic data of the sampled people in Lampang could be described as being male (53.2%), average aged 34.87, aged 15 – 25 (31.4%), graduated in bachelor’s degree (37.4%), earning 5,000 – 10,000 bath monthly personal income (35%), respectively. Secondary, on factors affecting people’ adoption data analysis was accomplished by using Logit model. This study found that improving entomology museum was the primary decisive factor increasing the likelihood for the people to adoption and support Entomology Research Center 1’s development by 21.94%. The next more influential factors likely to improve the chance for people’s in Lampang adoption by 5 – 15% included conservation insect project, notion of insect versus health system, Perception insect news, education, knowing Entomology Research Center, travel on Asian Highway number 2 (AH2). Meanwhile, monthly person income appeared to be able to increasing the likelihood for people’s adoption by only 4.15%. In the other hand, notion of insect versus nutrition appeared to be able to decreasing the likelihood for people’ adoption by 7.45%. In addition, this research was given an opportunity to comment about how to fixed obstruction of development. Reported by people in Lampang was found that the predominant problem and constraints as being distance from Muang Lampang district to Ngao district. In contrast, Reported by people in Lampang was found that the predominant way to support Entomology Research Center 1’s development as preferred travel to Entomology Research Center 1 more than donation.